Modulation of tissue factor expression by rapamycin and FK-506 in lipopolysaccharide-stimulated human mononuclear cells and serum-stimulated aortic smooth muscle cells - Ollivier, Véronique; Hammal, Soumeya; Ameziane, Nejma; Labro, Marie-Thérèse; de Prost, Dominique (Thrombosis and Haemostasis, 2005)
Inflammation is a key pathogenic component of atherosclerosis; it also promotes thrombosis, a process underlying acute coronary events and stroke. Cells present in atherosclerotic plaque show abnormal tissue factor (TF) expression. Macrolides, in addition to their antimicrobial properties, have antiinflammatory effects that might help prevent atherothrombosis. The aim of this study was to determine the effect of an immunosuppressant macrolide, rapamycin (Sirolimus), on the expression of TF and its inhibitor (TFPI) by monocytic cells (human blood mononuclear and THP-1 cells) and human aortic smooth muscle cells, in comparison with FK-506 and azithromycin. In monocytic cells, rapamycin and FK-506 inhibited LPS-induced TF activity, antigen and mRNA expression through a transcriptional mechanism involving NF-κB. In smooth muscle cells, rapamycin and azithromycin had no effect on serum-induced TF expression, while FK-506 increased serum-induced TF protein and mRNA expression. TFPI levels in the culture supernatants of serum-stimulated smooth muscle cells were not modified by any of the three macrolides. Rapamycin slightly inhibits TFPI induction by LPS in monocytic cells. In addition to its recently established efficacy in the prevention of stent restenosis, the inhibitory effect of rapamycin on theTF pathway might have interesting therapeutic implications.
Keywords: Rapamycin; monocytes; smooth muscle cells; tissue factor; macrolide